Long-term follow-up of abandoned transvenous defibrillator leads: a nationwide cohort study. Issue 7 (23rd May 2020) - Elgaard, Anders Fyhn; Johansen, Jens Brock; Nielsen, Jens Cosedis; Gerdes, Christian; Riahi, Sam; Philbert, Berit Thornvig; Haarbo, Jens; Melchior, Thomas Maria; Larsen, Jacob Moesgaard
Abstract: Aims : Commonly, a dysfunctional defibrillator lead is abandoned and a new lead is implanted. Long-term follow-up data on abandoned leads are sparse. We aimed to investigate the incidence and reasons for extraction of abandoned defibrillator leads in a nationwide cohort and to describe extraction procedure-related complications. Methods and results : All abandoned transvenous defibrillator leads were identified in the Danish Pacemaker and ICD Register from 1991 to 2019. The event-free survival of abandoned defibrillator leads was studied, and medical records of patients with interventions on abandoned defibrillator leads were audited for procedure-related data. We identified 740 abandoned defibrillator leads. Meantime from implantation to abandonment was 7.2 ± 3.8 years with mean patient age at abandonment of 66.5 ± 13.7 years. During a mean follow-up after abandonment of 4.4 ± 3.1 years, 65 (8.8%) abandoned defibrillator leads were extracted. Most frequent reason for extraction was infection (pocket and systemic) in 41 (63%) patients. Procedural outcome after lead extraction was clinical success in 63 (97%) patients. Minor complications occurred in 3 (5%) patients, and major complications in 1 (2%) patient. No patient died from complication to the procedure during 30-day follow-up after extraction. Conclusion : More than 90% of abandoned defibrillator leads do not need to be extracted during long-term follow-up. The most common indication for extraction is infection. Abandoned defibrillator leads can be extracted with high clinical success rate and low risk of major complications at high-volume centres.